Sobrevida de pessoas vivendo com HIV/AIDS na região dos Campos Gerais, Paraná 2008-2018 - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
A sample of people diagnosed with HIV / AIDS in the period from 2008 to 2018 was evaluated, with the live outcome at the end of the series and all deaths for the same diagnoses that occurred in this time interval, in residents of the Campos Gerais region, Paraná. This is a retrospective, exploratory and documentary cohort study. The target population consisted of 737 people, of which 56.9% corresponded to cases of death and 43.1% to living people diagnosed during the evaluation period. It was found that of the total cohort, 59.3% were male, with a mean age of 37.5 years, 77.6% of race and / or white skin color and 58.6% with elementary school. In relation to attendance to treatment, the frequency of 49.1% was found, with 21% of the people included in this research never having undergone specific treatment for HIV / AIDS. The median cohort survival was 8.8 years, with females 10.2 years and males 7.9 years; children up to 10 years old obtained 8.2 years, whereas those aged 11 to 20 years old had an average of 14.3 years old, while adults aged 41-60 years old and above 60 years old had a survival rate of 6.2 and 5.0 years old, respectively. Illiterates survived 7.1 years and those with high school or higher showed survival of 10.2 and 10.8 respectively; people without use of antiretrovirals had an average survival of 4.7 years. In the assessment of the relative risk of death, men registered RR 1.22; black and brown RR 1.18, and those diagnosed by December 31, 2013 (before treatment for all) RR 1.58. Despite the disparities between the subgroups evaluated, TARV has a significant impact on survival time when treatment is started early. Survival surveys make it possible to monitor imbalances in health care, treatment and care, situations that directly influence the quality and life expectancy of people living with HIV. Understanding that care needs to be attributed meaning, that is, meaningful for both professionals and PLHIV, it is necessary to break with the pseudology of the verticalization and superficiality of care, understanding health only if it is built collectively, contextualized, with plurality of knowledge focused on the uniqueness of the person. Only through interdisciplinarity, we will be able to involve those who are at the center of care, and maybe would be possible to reach a new stage in the life history of people living with HIV, and also being able to achieve transdisciplinarity soon.
Keywords: Análise de Sobrevida; HIV; AIDS; Antirretrovirais; Survival Analyses; Anti-Retroviral Agents; CNPQ::CIENCIAS DA SAUDE